2009
DOI: 10.3109/00016340903284901
|View full text |Cite
|
Sign up to set email alerts
|

Why do pregnant women stop exercising in the third trimester?

Abstract: Pre-pregnancy exercise was strongly related to exercise at late gestation. This study indicates a need for more information and motivation for moderate exercise before and throughout pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
4
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 27 publications
11
75
4
15
Order By: Relevance
“…In Sweden, as well as in the US, the general recommendation for adults, including pregnant women, for physical activity is at least 30 minutes of moderate intensity on most days of the week (Swedish National Institute of Public Health, 2010, Pate et al, 1995, Bell, 2006. Two Norwegian studies investigated the level of physical activity among pregnant women and reported levels of activity for regular exercisers of 81%, 69 % and 11% before pregnancy, in the first and in the third trimester respectively, whereas a British study found that 65 % of women in gestational week 13 achieved at least 30 minutes moderate or vigorous daily activity (Haakstad et al, 2007, McParlin et al, 2010, Haakstad et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, as well as in the US, the general recommendation for adults, including pregnant women, for physical activity is at least 30 minutes of moderate intensity on most days of the week (Swedish National Institute of Public Health, 2010, Pate et al, 1995, Bell, 2006. Two Norwegian studies investigated the level of physical activity among pregnant women and reported levels of activity for regular exercisers of 81%, 69 % and 11% before pregnancy, in the first and in the third trimester respectively, whereas a British study found that 65 % of women in gestational week 13 achieved at least 30 minutes moderate or vigorous daily activity (Haakstad et al, 2007, McParlin et al, 2010, Haakstad et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Tiredness and body complaints such as feeling too fat (Fell et al 2009, Haakstad et al 2009) were reasons used to not attend exercise classes or to stop an activity altogether. Such symptoms will be ever present in some individuals, the dilemma is to find a way that individuals can exercise at any point when they feel able; for example as stated by one of the women, the Wii Fit has the added bonus of being present in the home which encouraged use.…”
Section: Discussionmentioning
confidence: 99%
“…Common physical symptoms of pregnancy such as feeling too tired, feeling uncomfortable, feeling nauseous or being sick, were seen as contributing factors for reducing or not partaking in exercising (Symons Downs and Hausenblas 2004, Cramp and Bray 2009, Duncombe et al 2009, Haakstad et al 2009, Melzer et al 2010, Foxcroft et al 2011. Discouragement from family members was also reported as a barrier to continuing exercise as the pregnancy progressed (Clarke and Gross 2004).…”
Section: Barriers To Exercising During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Fizičko vežbanje pre trudnoće pokazalo se kao snažnan prediktor redovnog vežbanja u toku trudnoće [Haakstad 2009]. Međutim, znatan broj žena prestane sa vežbanjem čim trudnoća bude potvrđena [Liu 2011].…”
Section: Diskusija Studije Determinanti Zdravstvenogunclassified